Pengolahan Es Krim Fungsional dengan Penambahan Ekstrak Biji Pala Muda pada UMKM Asaompu Production di Kota Ternate - Lumbessy, Abd. Syukur; Nurjana Albaar; Hamidin Rasulu (Program Studi Kehutanan, Universitas Khairun, 2025)
This Community Service (PKM) program aims to enhance the innovation capacity of Asaompu Production UMKM in Ternate City through the development of functional ice cream with the addition of young nutmeg seed (Myristica fragrans) extract. Young nutmeg is known to contain bioactive compounds such as myristicin, eugenol, and safrole, which act as antioxidants, antimicrobials, and flavor enhancers. The implementation method includes socialization, technical training in ice cream formulation, hygienic production assistance, organoleptic testing, and product branding and marketing strategies. The results showed an improvement in partners’ skills in ice cream processing, product diversification based on local resources, and high consumer acceptance of the new functional ice cream with nutmeg extract. This program contributes to strengthening UMKM competitiveness and promoting local commodities as value-added functional foods.